2020
DOI: 10.1111/aos.14375
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oedema in central retinal artery occlusion develops as a function of time

Abstract: PurposeTime is the key criterion in the management of non‐arteritic central retinal artery occlusion (NA‐CRAO). However, the precise onset of vision loss is often difficult to determine. This study aimed to evaluate the temporal changes of retinal thickness in acute NA‐CRAO and the potential of this parameter to be used as a surrogate marker to estimate the onset of retinal ischaemia.MethodsOptical coherence tomography was used to continuously assess retinal thickness and oedema progression rate in six porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…In previous studies, we presented the temporal changes of retinal thickness in acute CRAO patients [ 5 , 16 ]. We showed with a sensitivity of 100% and a specificity of 94.3% that RRTI is a valuable surrogate parameter to determine if ischemia onset was within the last 4.5 hours [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we presented the temporal changes of retinal thickness in acute CRAO patients [ 5 , 16 ]. We showed with a sensitivity of 100% and a specificity of 94.3% that RRTI is a valuable surrogate parameter to determine if ischemia onset was within the last 4.5 hours [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, CRAO is a clinical diagnosis, but as unfortunately clinical signs such as retinal edema and a cherry red spot may have not evolved in the very early phase, pathognomonic signs on OCT scans can provide valuable information about CRAO. An increase in retinal thickness for example is a characteristic feature, for which a temporal correlation has been shown recently ( 16 , 17 ). Similarly, a rise in optical intensity in the affected eye can be observed ( 9 , 11 , 12 , 19 ), but the temporal dynamics have yet been unknown.…”
Section: Discussionmentioning
confidence: 79%
“…Although it is well known that acute CRAO induces a retinal oedema, data dealing with the exact temporal dynamics of the retinal thickness increase, however, is scarce (Falkenberry et al 2006; Shinoda, Yamada & Matsumoto 2008; Chen, Hwang & Chen 2011; Cornut et al 2012). Our recent publication found near‐linear retinal thickness increase as a function of time in the very acute phase (first 9 hr) of CRAO, which gave reason to us to investigate this possible biomarker's behaviour over the first 48 hr after ischaemia onset in the present study (Ochakovski et al 2020). We hypothesized that RRTI might be useful to be used as surrogate marker to determine whether a patient is within the therapeutic window of 4.5 hr – the period of time where a reperfusion therapy might be beneficial (Schrag et al 2015; Schultheiss et al 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Nonetheless, the exact temporal dynamics of the natural course of retinal thickness changes in the acute phase of CRAO are not well described and, so far, remain inconclusive. Recently, we have shown that the retinal thickness increase shows a near‐linear progression rate within the first 9 hr after ischaemia onset measured by optical coherence tomography (OCT) (Ochakovski et al 2020). In this context, the objective of this study was to quantitatively assess the temporal changes in retinal thickness within the first 48 hr and to determine the ability of OCT‐based retinal thickness analysis to specify the time of ischaemia onset in acute CRAO (≤ 8 hr) patients, which in the future may imply important consequences for possible reperfusion concepts, such as intravenous thrombolysis.…”
Section: Introductionmentioning
confidence: 99%